Towards the Effective Motivation: Adaptation of the Situations in School Questionnaire (SISQ) to Lithuanian Educational Context - Gabrialavičiūtė, Ingrida; Raižienė, Saulė; Garckija, Renata (Psichologija, 2022)
To help teachers understand their role in students’ motivation and well-being, the researchers within SDT (Aelterman et al., 2019) have recently proposed a Circumplex model – the integrative and fine-grained approach to analyze the variety and interactions of (de)motivating teaching styles. The purpose of the current study is to adapt the student version of the Situations in School Questionnaire based on the Circumplex model for Lithuanian educational context. 715 seventh- and eighth-grade students (50.9% girls, Mage=13.42 years) from ten Lithuanian schools participated in the study. The SISQ was used to measure (de)motivating teaching styles, also behavioral and cognitive engagement in learning as well as well-being (positive and negative emotions, satisfaction with math classes) were assessed as indicators of students’ functioning. Multidimensional scaling, confirmatory factor analysis, and correlational analysis showed the match of the SISQ structure to the Circumplex model. (De)motivating teaching can be best graphically represented by a two-dimensional configuration that differed in terms of need support and directiveness. Correlations between eight subareas and indicators of students’ functioning followed a systematic sinusoid pattern, suggesting a gradual effect of teaching on students’ outcomes. With the adaptation being successful, student version of the SISQ can be used in Lithuanian educational context.